Cognitive media theory - Nannicelli, Ted; Taberham, Paul (New York Routledge, 2014)
"The question of what bearing scientific inquiry has upon the humanities is the subject of an important, ongoing debate in film and media studies. In the latest addition to the AFI Film Readers series, Cognitive Media Theory presents a case that the theorization of film and media spectatorship needs to take current empirical research in the sciences into consideration, and to show how empirical research informs film and media studies. Exploring topics that range from color perception and moral engagement to our cognitive response to humor, Cognitive Media Theory offers film and media scholars and advanced students an introduction to current cognitive theory through original essays that critically reflect upon the current state of the field. Contributors address key topics, genres, and media forms, and present the findings of specific experiments and case studies conducted across film, television, and video games"--|cProvided by publisher
Introduction: contemporary cognitive media theory / Ted neuroscience and the naturalized aesthetics of film / Murray Smith -- Evolutionary film theory / Malcolm Turvey -- The geography of film viewing: what are the implications of cultural-cognitive differences for cognitive film theory? / Daniel Barratt -- Audiovisual correspondences in Sergei Eisenstein's Alexander Nevsky: a case study in viewer attention / Tim J. Smith -- Engaged and detached film viewing: exploring film viewers' emotional action readiness / Ed S. Tan -- Coloring the animated world: exploring human color perception and preference through the animated film / Kaitlin L. Brunick and James E. Cutting -- Mood and ethics in narrative film / Carl Plantinga -- Effects of entertaining violence: a critical overview of the general aggression model / Dirk Eitzen -- A general theory of comic entertainment: arousal, appraisal, and the PECMA flow / Torben Grodal -- Postcolonial humor, attachment, and Yasujiro Ozu's Early summer / Patrick Colm Hogan -- Avant-garde film in an evolutionary context / Paul Taberham -- Cognitive theory and the individual film: the case of Rear window / William Seeley and Noël Carroll -- Cognitive theory and video games / Andreas Gregersen -- Blinded by familiarity: partiality, morality and engagement with television series / Margrethe Bruun Vaage -- Coming out of the corner: the challenges of a broader media cognitivism / Greg M. Smith.
Includes bibliographical references (pages 303-330) and index.
Keywords: Mass media; Humanities -- Research; Social sciences -- Research